Enhancement of the execution group's maintenance monitoring system - Torres, Jan Nico D. (Animo Repository, 2022)
This action research strived to improve the monitoring system of the Integrated Subsurface-Execution Group. Through the co-inquiry and root-cause analysis phase, my collaborators and I identified the issues in the form of outdated monitoring sheet with lack of robust quality data. We decided to improve the monitoring sheet by making it online and overhauling its data. To perform this improvement, we applied the ADKAR model to serve as the guidance throughout the change process. We performed two cycles of action research to achieve our objectives. The first cycle involved creating an online monitoring sheet that listed all of Execution Group’s drilling equipment. This sheet exhibited key data used for identifying the status and condition of each line item. In the second cycle, we tried to improve on the monitoring sheet we produced. When we identified that there are purchase requisitions rejected by our buyers due to lacking Technical Data Sheets (TDS), we integrated the TDS information with our monitoring sheet. This served two purposes, first is that the monitoring sheet became more holistic, and the viewers had more key information which can aid their decision making. Second is that the Maintenance Team can utilize the monitoring sheet as the basis and source of data of their purchase requisition requests, which subsequently can be used by the buyers as a counter check. I was also able to reflect on the content, process, and premise of the first and second cycles of this action research. We were able to apply our solutions to effectively come up with a useable monitoring sheet for our stakeholders in the company. Lastly, I discussed the extrapolation of the results of this action research for future action researchers.